Study on the preparation of flame retardant plywood by intercalation of phosphorus and nitrogen flame retardants modified with Mg/Al-LDH. (17th April 2023) - Deng, Chao; Liu, Yang; Jian, Hao; Liang, Yuqing; Wen, Mingyu; Shi, Junyou; Park, Heejun
Highlights: Two new organic-inorganic flame retardants were synthesized and characterized. In addition, two phosphorus-nitrogen flame retardants were obtained by synthesis of Pyrovatex CP with urea and melamine, respectively, and were modified by intercalation with Mg/Al-LDH. It was applied to formaldehyde-free API adhesives to prepare flame-retardant plywood materials. The Mg/Al-LDH was prepared by the ion exchange method, and the unique laminated structure exerts a synergistic flame retardant effect. Moreover, this method has little impact on the strength of plywood. The synthesized obtained flame retardant can exert the synergistic effect of phosphorus, nitrogen, and inorganic compounds, which can promote the formation of a cohesive phase and provide a continuous and compact char layer to stop the further burning of plywood. It provides an environmental-friendly and simple method to prepare flame retardant wood materials for construction applications. Abstract: Wood-based material is widely used as a construction material due to its good mechanical properties, low production costs, and sustainability. However, its flammability limits applications in the field of construction. In this study, the two new phosphorus-nitrogen flame retardants were intercalated and modified with Mg/Al-LDH (abbreviated as UCPR-LDH and MCPR-LDH) and the resulting organic-inorganic synergistic flame retardants were prepared for formaldehyde-free flame retardant plywood. The results showed that the best intercalation effect was achieved with a mass ratio of 4:1 for LDH to UCPR and 2:1 for LDH to MCPR. The cone calorimetry test reveals that the total heat release of UCPR-LDH plywood is less than 8 MJ/m 2 during 300 s of combustion, and the MCPR-LDH plywood reduces total smoke production by 70.6%. Meanwhile, the flame retardancy index (FRI) for the modified plywood was all "good". Due to the synergistic effect of phosphorus and nitrogen flame retardants and LDH, the modified plywood exhibited good carbon-forming performance and higher graphitization during combustion, which play a role in cohesive phase protection and impeding the transfer of heat and combustible materials. In addition, the bonding strength of flame retardant-modified plywood decreased a little, but still meets industry standards. This work provides an environmental-friendly and simple method to prepare flame-retardant wood materials for construction applications.